Penerapan Metode Bernyanyi dalam Meningkatkan Pengetahuan dan Keterampilan Anak Usia Dini - Marwiyah; Sri Wahyuni (GHULAMUNA: JOURNAL OF EARLY CHILDHOOD EDUCATION, 2023)
This research is motivated by the lack of variety in teaching methods during the delivery of material, leading to monotonous teaching practices. The use of inappropriate methods can make learning boring for children and less motivating for them to apply what has been taught. To address this problem, the singing method is used. The research method employed in this study is a qualitative descriptive approach, with the object of research being the implementation of the singing method to enhance knowledge and skills at TK Lam Alif Bicabbi Dungkek. Data were collected through observation, interviews, and documentation. The research findings show that learning through the singing method involves the following steps: (1) Selecting songs that align with the theme, (2) Using melodies that are easily understood by the participants, (3) Introducing the songs to the children, and (4) Singing the songs together with appropriate body movements. The study illustrates that these four steps in the implementation of the singing method during the learning process for early childhood can be considered as one of the alternatives in applying the singing method. Based on the research results, it can be concluded that the implementation of the singing method enhances the knowledge and skills of early childhood learners, and it improves the teacher's ability to deliver the lessons effectively.